Circularized Chromosome with a Large Palindromic Structure in Streptomyces griseus Mutants - Uchida, Tetsuya (American Society for Microbiology, 2004)
Streptomyces linear chromosomes display various types of rearrangements after telomere deletion, including circularization, arm replacement, and amplification. We analyzed the new chromosomal deletion mutants Streptomyces griseus 301-22-L and 301-22-M. In these mutants, chromosomal arm replacement resulted in long terminal inverted repeats (TIRs) at both ends; different sizes were deleted again and recombined inside the TIRs, resulting in a circular chromosome with an extremely large palindrome. Short palindromic sequences were found in parent strain 2247, and these sequences might have played a role in the formation of this unique structure. Dynamic structural changes of Streptomyces linear chromosomes shown by this and previous studies revealed extraordinary strategies of members of this genus to keep a functional chromosome, even if it is linear or circular.